Serum vitamin D levels of Oral squamous cell carcinoma patients of KPK - Ahmad, Sana; Khan, Abbas Saleem; Awais, Syed Muhammad; Raza, Muhammad; Farooq, Syed Omar (ADVANCES IN BASIC MEDICAL SCIENCES, 2023)
Objective The objective of this study is to estimate serum levels of vitamin D in oral squamous cell carcinoma cases. Methodology It was a multicenter study conducted at the Department of Pathology, Peshawar Medical College (PMC) and Prime Teaching Hospital. The specimens were collected from Department of Oral Pathology; Peshawar Dental College (PDC), Institute of Radiotherapy and Nuclear Medicine (IRNUM), Peshawar; Khyber College of Dentistry (KCD), Peshawar; Bacha Khan Dental College, Mardan. The study consisted of 60 diagnosed cases of OSCC. Blood samples were collected from all 60 participants. Serum vitamin D levels were estimated by Electro-chemiluminescence Immunoassay. The data then was statistically analyzed by Statistical Package for the Social Sciences (SPSS) version 20. The statistical differences between the two groups was calculated by using student t test. Statistical significance was determined at p value ≤ 0.05. Results The mean age was 50.27 years with a male to female ratio 2:3. In the oral squamous cell carcinoma patients (n=60), all the participants were deficient in vitamin D with vitamin D levels ≤ 20 ng/ml. Mean serum vitamin D level was 10.78ng/ml, among these 24 were males and 36 were females. Conclusion Our study showed deficiency of serum vitamin D in all the cases of OSCC patients Key words: Vitamin D, Oral squamous cell carcinoma, oral cancers, serum levels